2004
DOI: 10.4067/s0034-98872004000300007
|View full text |Cite
|
Sign up to set email alerts
|

Características de la tuberculosis en pacientes mayores de 65 años en el área sanitaria de Cádiz (España)

Abstract: Characteristics of tuberculosis in patients older than 65 years in the sanitary area of Cadiz (Spain) (Rev Méd Chile 2004; 132: 325-30).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
1
2
0
5
Order By: Relevance
“…These data corroborate the observation that tuberculosis is a disease that affects the individual in the most productive period of his/her life [1]. However, recent studies show a dislocation of tuberculosis incidence from adults in general to the elderly [8,9]. The observed higher incidence of whites in relation to non-whites may be a consequence of the profile of the population of this region and not to a racial predisposition toward tuberculosis.…”
Section: Risk Factors* Discussionsupporting
confidence: 79%
“…These data corroborate the observation that tuberculosis is a disease that affects the individual in the most productive period of his/her life [1]. However, recent studies show a dislocation of tuberculosis incidence from adults in general to the elderly [8,9]. The observed higher incidence of whites in relation to non-whites may be a consequence of the profile of the population of this region and not to a racial predisposition toward tuberculosis.…”
Section: Risk Factors* Discussionsupporting
confidence: 79%
“…Patients aged 65 and older represent 16% to 40% of patients admitted with TB in the developed word 3,4 . It has been suggested that TB in people aged 65 and older differs from disease presenting in younger patients 5–7 .…”
mentioning
confidence: 99%
“…2 Patients aged 65 and older represent 16% to 40% of patients admitted with TB in the developed word. 3,4 It has been suggested that TB in people aged 65 and older differs from disease presenting in younger patients. [5][6][7] These differences might account for unusual clinical manifestations and a delay in diagnosis and treatment.…”
mentioning
confidence: 99%
“…de 80 años es cercana al 7%, al igual que otras cohortes evaluadas en España y taiwán reportan prevalencias entre el 8 y el 10%, siendo similar a lo esperado (18,19), respecto al sexo, no hubo diferencia alguna, lo cual difiere de la distribución de este en la tuberculosis, en la que hay mayor prevalencia en el sexo masculino (1,20). Contacto reciente con tuberculosis Con relación a las manifestaciones clínicas de los pacientes, los síntomas (tos, fiebre, sudoración nocturna y pérdida de peso) estuvieron presentes en menos de la mitad de los casos, lo que obliga al profesional de la salud a tener un alto nivel de sospecha.…”
Section: Los Hallazgos Evidencian Que La Prevalencia Institucional Deunclassified